2018
DOI: 10.4081/monaldi.2018.967
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation versus minimal sedation during endobronchial ultrasound transbronchial needle aspiration

Abstract: The sedation plays an important role in the endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) procedure. The sedation can be Minimal (anxiolysis), Moderate (conscious sedation) or Deep. The ACCP guidelines suggest that moderate or deep sedation (DS) is an acceptable approach. In fact, several studies compare moderate versus deep sedation, but no study has been carried out to compare deep sedation versus minimal. We carried out a retrospective study to compare the Deep versus Minimal sedatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…All but one retrospective studies reported that diagnostic yield and patient tolerance under deep propofol sedation was equivalent to that under moderate midazolam sedation [37][38][39][40]. Prospective randomized control trials comparing the use of propofol for general anesthesia and midazolam for moderate sedation were also comparable in terms of diagnostic yield, major complications, and patient tolerance [31,41].…”
Section: Discussionmentioning
confidence: 99%
“…All but one retrospective studies reported that diagnostic yield and patient tolerance under deep propofol sedation was equivalent to that under moderate midazolam sedation [37][38][39][40]. Prospective randomized control trials comparing the use of propofol for general anesthesia and midazolam for moderate sedation were also comparable in terms of diagnostic yield, major complications, and patient tolerance [31,41].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we showed that the type of sedation did not influence our results. In fact, several studies showed that the type of sedation does not influence the diagnostic yield, sensitivity and accuracy [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It is used to evaluate mediastinal and hilar lymph nodes and effectively determine the stage of lung cancer [ 1 6 ]. It is also recommended to diagnose suspected cases of lymphoma, sarcoidosis, and tuberculosis [ 2 , 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While FOB can be performed routinely only under mild sedation or local anesthesia, EBUS-TBNA can be performed in a wide range from minimal sedation to general anesthesia [ 5 13 ]. Ideal sedation for EBUS-TBNA is aimed to increase diagnostic efficiency, prevent complications, and improve patient comfort by providing adequate procedural tolerance [ 3 , 7 , 8 , 13 16 ]. The choice of sedation type varies according to institutional resources and approaches.…”
Section: Introductionmentioning
confidence: 99%